2008
DOI: 10.1590/s1415-47572008000200006
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome divergence and NOR polymorphism in Bryconamericus aff. iheringii (Teleostei, Characidae) in the hydrographic systems of the Paranapanema and Ivaí Rivers, Paraná, Brazil

Abstract: Cytogenetic studies were carried out in three populations of Bryconamericus aff. iheringii from two hydrographic systems of the Paranapanema and Ivaí Rivers, separated by a watershed, both belonging to the upper Paraná River basin. Specimens had a constant diploid number 2n = 52 chromosomes. However, three karyotype formulae were identified in the three populations: B. aff. iheringii from the Maringá stream had 12M+18SM+8ST+14A (FN = 90); specimens from Keller River showed 8M+28SM+6ST+10A (FN = 94) and specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 25 publications
(22 reference statements)
5
28
0
Order By: Relevance
“…However, the single NOR system has been observed in 3 populations of B. aff. iheringii (Paintner-Marques et al 2003;Capistano et al 2008 and through the present study). According to Galetti Jr. (1998) having a single pair of chromosomes bearing 45S rDNA is considered a primitive character for fish.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…However, the single NOR system has been observed in 3 populations of B. aff. iheringii (Paintner-Marques et al 2003;Capistano et al 2008 and through the present study). According to Galetti Jr. (1998) having a single pair of chromosomes bearing 45S rDNA is considered a primitive character for fish.…”
Section: Resultssupporting
confidence: 55%
“…iheringii from the Três Bocas Stream also showed the same chromosomal NOR variations. Capistano et al (2008) also observed a number variation from 2-4 AgNOR chromosomes, both inter and intra-individual with markings in the region of the short and/or on the long arm in Bryconamericus aff. iheringii collected in the Maringá Stream (cytotype I) and in the Keller River (cytotype II), indicating a system of multiple NORs for these 2 populations.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…As occur with C-bands, the genus Astyanax also shows distinct patterns in relation to NORs, with single and multiple systems and with both intra-and inter-specific variations in number and locations on the chromosomes (Kavalco and Moreira-Filho, 2003;Pazza et al, 2006;Capistano et al, 2008;Kavalco et al, 2011). In this study a multiple marking system was only found in Astyanax aff.…”
Section: Discussionmentioning
confidence: 44%